Making Black America : through the grapevine [videorecording (DVD)] - Isham, Sultana (PBS, 2022)
The four-part series hosted by Henry Louis Gates, Jr., chronicles the vast social networks and organizations created by and for Black people beyond the reach of the "White gaze." The series recounts the establishment of the Prince Hall Masons in 1775 through the formation of all-Black towns and business districts, Historically Black Colleges and Universities, destinations for leisure, and the social media phenomenon of Black Twitter. Professor Gates sits with noted scholars, politicians, cultural leaders, and old friends to discuss this world behind the color line and what it looks like today. It takes viewers into an extraordinary world that showcased Black people's ability to collectively prosper, defy white supremacy and define Blackness in ways that transformed America itself.